PERENCANAAN JALUR INTERPRETASI BIRDWATCHING DI HUTAN LINDUNG ANGKE KAPUK, JAKARTA (Birdwatching Interpretive Trail Planning in Angke Kapuk Protected Forest, Jakarta) - Sulistio, Ficky Rifky; Muttaqin, Zainal; Sasongko, Dwi Agus (Jurnal Nusa Sylva, 2023)
Birdwatching is a specialized ecotourism activity where visitors observe and photograph birds. It can serve as an educational tool for the conservation of birds. The aim of this research is to identify the diversity of bird species and create an interpretive trail for birdwatching in the Angke Kapuk Protected Forest area. Avenza Maps was used to record encountered bird species. Data on bird species diversity were analyzed using the Shannon-Wiener diversity index, and encounter rates were calculated to determine the number of bird species observed within a specific time period. This data was then used to categorize the abundance of bird species. Data processing was done using QGIS 3.26.1 and Adobe Photoshop. The results of the Birdwatching Interpretive Trail Planning research identified a total of 30 bird species from 24 families. Three bird species were found to be protected under Minister of Environment and Forestry Regulation No. 106 of 2008, and one species was classified as Vulnerable according to the IUCN Red List. Bird species were categorized as Abundant (10 species), Frequent (3 species), Uncommon (8 species), and Rare (9 species). The research area had three trails with distances of 120 meters, 266 meters, and 200 meters. Some issues observed regarding trail conditions included damage to supports causing interruptions in some parts of Trail 3 and litter found on Trails 1 and 2.